Where night is day : the world of the ICU - Kelly, James, 1948- (Culture and politics of health care work., 2013)
"This book describes the hour-by-hour, day-by-day rhythms of an intensive care unit in a teaching hospital in New Mexico. Written by a nurse, Where Night Is Day reveals the specialized work of ICU nursing and its unique perspective on illness, suffering, and death. It takes place over a thirteen-week period, the time of the average rotation of medical residents through the ICU. As the author, James Kelly, reflects on the rise of medicine, the nature of nursing, the argument of care versus cure, he offers up an intimate portrait of the ICU, the patients who live and/or die there, and the medical professionals who work there"--Publisher's Web site.